2010
DOI: 10.1517/14656561003601994
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring adherence rates in glaucoma patients using the Travatan Dosing Aid. A 6-month study comparing patients on travoprost 0.004% and patients on travoprost 0.004%/timolol 0.5% fixed combination

Abstract: The typical nonadherent patient is elderly. TDA records indicate that only a minority of patients are really adherent: predictive models to screen for poor adherence are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…A number of factors, such as inadequate patient education, complexity of treatment regimens, side effects of medications, and challenges with regular and correct instillation of eye drops, have been identified as possible barriers to optimal adherence. 40 43 Studies have suggested that persistence with glaucoma medications is also low when multiple medications are required. 44 46 Fixed-combination therapies, including BBFC, can potentially alleviate a number of these issues.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors, such as inadequate patient education, complexity of treatment regimens, side effects of medications, and challenges with regular and correct instillation of eye drops, have been identified as possible barriers to optimal adherence. 40 43 Studies have suggested that persistence with glaucoma medications is also low when multiple medications are required. 44 46 Fixed-combination therapies, including BBFC, can potentially alleviate a number of these issues.…”
Section: Discussionmentioning
confidence: 99%
“…Rossi et al. (2010) monitored prostaglandin therapy using the same dosing aid and qualified 46.4% of 56 patients to have ‘poor adherence’.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Patient adherence with IOP-lowering treatment is crucial for the successful medical management of glaucoma; however, adherence with glaucoma medications is typically low and decreases with time. [8][9][10] Adherence is influenced by many patient-and treatment-related variables, and treatment complexity (ie, number of individual medications and daily doses) is one of the only modifiable factors associated with suboptimal treatment adherence. For example, compared with combination medications, treatment regimens using multiple individual medications are associated with lower treatment adherence.…”
mentioning
confidence: 99%